KARAKTERISTIK PENDERITA RETINOPATI DIABETIK YANG DIRAWAT INAP DI RSUD DR. PIRNGADI KOTA MEDAN TAHUN 2013-2016 - Ade Ayu Lanniari Harahap; Hiswani .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Diabetic retinopathy (DR) is chronic complication of Diabetes Mellitus (DM) which the main causes of decreased vision and blindness in diabetes patients. World Health Organization (2016) reported that prevalence of retinopathy in person with DM in 2012 is 35% while proliferative retinopathy is 7%. In Indonesia, the prevalence of diabetic retinopathy and blindness in Indonesian adult with type 2 diabetes in 2017 is 42%. The proportion of diabetic retinopathy patients in RSUP H Adam Malik Medan in 2012-2015 is 36,7%. The purpose of this study was to determine the characteristics of diabetic retinopathy are hospitalized in RSUD dr. Pirngadi Medan city in 2013-2016, Thus research is descriptive with case series design. The population of this research is 105 data of diabetic retinopathy patients are hospitalized in RSUP H Adam Malik Medan in 2013-2016, the sample is the same as the population. The kind of data was secondary and analize by Chi-Square test and Fisher’s Exact test. The result showed the higest proportion of diabetic retinopathy patients at ages 46-65 years (67,6%), women (54,3%), Moslem (74,2%), secondary education ((68,6%), housewife ((48,6%), origin from Medan city (69,5%), type 2 diabetes (94,3%), HbA1c level ≥6,5% (78,1%), RDNP degree (71,4%), other complication ulcus diabetic (20%), askes/BPJS (58,1%), average length of stay 8,68 hari. There was a difference between HbA1c level by the degree of diabetic retinopathy (p=0,004). To the Government and the hospital to do the efforts of prevention, promotion and screening for diabetic patients. The diabetic patients should do routine blood glucose levels control and to diabetic retinopathy patients check the eyes at least once a year. Need to do further research about diabetic retinopathy to be a reference for review the characteristics of diabetic retinopathy in Indonesia and early detection to reduces diabetic retinopathy.